Artificial neural networks in diagnostic system for purifying fumes installation - Bańka, Stanisław; Jaroszewski, Krzysztof (Computer Assisted Methods in Engineering and Science, 2007)
The purpose of the paper is to present solution to design additional diagnostic system for, based on cutting-edge technology, purifying fumes installation. Neural networks, which determine the core of the system, were used as predictive models. Designed very efficient neural structures have served to build simulative diagnostic advisory system.